Design and fabrication of bluetooth solar grass trimmer - Nur Arissa, Mohd Fadelah (2019)
Gas powered lawn mower are one of devices that contribute to the pollution especially air pollution. If using electrical powered, for sure it consumes large amount of energy for the working to move the cutting blades and the wheels. For the solution to nowadays problem as the mowers use fuel which could pollute the environment and produce lousy noise, this project is implemented with the objective to design and fabricate a Bluetooth Solar Grass Trimmer that easy to handle. A solar powered grass trimmer controlled by Bluetooth device with a systematic photovoltaic (PV) solar system was built in together with the trimmer as the source to reduce the manpower and usage of electricity. The process start by identify the problems occurred in the community. Then, proceed with the design constructed by using NX10 and choosing the right material for the trimmer. The materials were assembles to build the trimmer and were test at the field. After done the assembly part and the program are successfully installed, Bluetooth Solar Grass Trimmer is able to move forward and reverse by using dc geared motors. After that, the battery needs to be recharge again to power up the Arduino and motor driver. The grass trimmer also can be control by using the RC Bluetooth Controller. The application can be downloaded in the android phone. It is easier as it can be control from afar and safe for the children. The idea of invented Bluetooth Solar Grass Trimmer now can be used in home lawn area as it is portable and can be operates without human energy.